The Roman Lower Danube frontier : innovations in theory and practice - Hanscam, Emily; Karavas, John (2023)
Over the past few decades, there has been a significant amount of research on the Roman Lower Danube frontier by international teams focusing on individual forts or broader landscape survey work; collectively, this volume represents the best of this collaboration with the aim of elevating the Lower Danube within broader Roman frontier scholarship.